Computer vizualization for the theatre : 3D modelling for designers - Carver, Gavin; White, Christine (Boston, Mass. : Focal Press, 2003)
Useful for theatre designers using 3D software for computer visualisation in the theatre, this book presents a guide to the creative design process and provides an introduction to the use of computers in live performance. It covers the software packages and techniques for 3D modelling alongside creative ideas and concepts for working in 3D space.
Contents: Introduction; Setting the scene: contexts and approaches; Outlining the software and its development; Thinking about the hardware: an overview of relevant technologies; Navigating the computer space; The basics of modelling; The basics of materials; The basics of lighting; The rule of change - scenographic improvisation; Composition, cameras, rendering and resolution; Advanced modelling; The design over time: storyboards and animations; Project management; Conclusion; Bibliography; Glossary
Includes bibliographical references (p. [213]-217) and index
Keywords: Theaters -- Stage-setting and scenery -- Computer-aided design